Time delay during intra-base proton tunneling in the guanine base of the single stranded DNA - Özçelik, Elif; Akar, Demet Eda; Zaman, Semih; Demir, Durmuş (Progress in biophysics and molecular biology, 2022)
Spontaneous point mutations are one of the main actors in evolution, and the tautomerization of organic bases in the DNA is hypothesized to be the underlying mechanism of this crucial process. Tautomerization can be induced by proton tunneling, and if it occurs in single-stranded DNA (ssDNA) during the replication process, tautomerized bases might give rise to a mismatch, which will eventually defect the genetic code. In the present work, we report on the tautomerization time in the guanine base of the ssDNA. The model we use includes an intra-base tunneling mechanism such that time tunneling (delay time) is estimated to be around a few pico-seconds. The time delay is found to be biologically relevant which indicates that it is long enough to induce point mutations. Our results close a gap in the literature and sheds light on the importance of point mutations originating from quantum effects in the ssDNA.